Evaluation of relationship of body mass index with severity of cholecystitis - Chauhan, Varun V.; Shah, Bhushan A.; Mahadik, Shivaratna J.; Videkar, Rohan P. (International Surgery Journal, 2019)
Background: Obesity is an established risk factor for gall stone disease. Male sex has also been recently cited as a risk factor for severe symptomatic cholelithiasis. As a possible cause of several difference in regards to the severity of cholecystitis, many physiological differences between the two sexes can be examined. Many studies have been done on the risk factors for developing the gall bladder disease explaining its polygenic nature It is postulated that the total body fat, the main value of which is significantly higher for females than males, may contribute to this sex difference. Only a couple of studies are available on BMI and its effect on severity of cholecystitis hence depicting the need for this study in our setup. Methods: This is a prospective study carried out on 70 patients for cholecystitis whose weight and height measurements had been recorded on admission. Patients were placed in either group-Obese (BMI e” 25kg/m2) or Non-Obese (BMI <25kg/m2). The association between BMI and severity of cholecystitis was investigated. Results: 18% of the laparoscopic cholecystectomy surgeries required conversion to open cholecystectomy due to reasons like severe adhesions to an adjacent organ, etc. Pain in abdomen (100%) was the commonest complaint and was present in all the patients followed by dyspepsia (44%).69% of patients were having complaints for more than 72 hours. No significant difference observed among mean BMI of different grades of severity (p=0.963). Conclusions: There is negative correlation between BMI and grade of severity of cholecystitis and BMI is not a predictor for the conversion from laparoscopic to open cholecystectomy.